2014
DOI: 10.1159/000358868
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Acute Generalised Exanthematous Pustulosis after Unprotected Sexual Intercourse on Holidays in Bali

Abstract: We present the case of a 43-year-old man with a clinical diagnosis of acute generalised exanthematous pustulosis in the setting of a recent 9-day holiday to Bali, Indonesia, to visit a female partner whom he had visited five times this year for unprotected sexual intercourse and from whom he had contracted a sexually transmitted infection. He also reports having taken some Indonesian cold and flu medications and ibuprofen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Well‐known triggers of AGEP include antibiotic drugs such as β‐lactams, clindamycin, and macrolides. Ibuprofen has only very rarely been described as a cause of AGEP . This is the first case report in which the diagnosis of AGEP caused by ibuprofen has been confirmed by positive patch test results, suggesting a type IV T cell‐mediated pathogenesis.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Well‐known triggers of AGEP include antibiotic drugs such as β‐lactams, clindamycin, and macrolides. Ibuprofen has only very rarely been described as a cause of AGEP . This is the first case report in which the diagnosis of AGEP caused by ibuprofen has been confirmed by positive patch test results, suggesting a type IV T cell‐mediated pathogenesis.…”
Section: Discussionmentioning
confidence: 74%
“…This is the first case report in which the diagnosis of AGEP caused by ibuprofen has been confirmed by positive patch test results, suggesting a type IV T cell‐mediated pathogenesis. In the published case reports, the diagnosis was made clinically, histologically, or on the basis of a basophil activation test . The authors claimed that patch testing may trigger the original rash, but we found only a localized rash and pustulosis in the area of direct contact with ibuprofen.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation